The effect of pale, soft and exudative (PSE) pork and fat grading on physico-chemical characteristics of low fat bacon - De Kock, Henrietta Letitia (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Food Production and Processing))--University of Pretoria, 2005.